A FreeSurfer-compliant consistent manual segmentation of infant brains spanning the 0–2 year age range - de Macedo Rodrigues, Katyucia; Ben-Avi, Emma; Sliva, Danielle D.; Choe, Myong-sun; Drottar, Marie; Wang, Ruopeng; Fischl, Bruce; Grant, Patricia E.; Zöllei, Lilla (Frontiers in Human Neuroscience, 2015)
We present a detailed description of a set of FreeSurfer compatible segmentation guidelines tailored to infant MRI scans, and a unique data set of manually segmented acquisitions, with subjects nearly evenly distributed between zero and two years of age. We believe that these segmentation guidelines and this dataset will have a wide range of potential uses in medicine and neuroscience.